Quantification of cerebral metabolites in glioma patients with proton MR spectroscopy using T2 relaxation time correction - Isobe, Tomonori; Matsumura, Akira; Anno, Izumi; Yoshizawa, Takashi; Nagatomo, Yasushi; Itai, Yuji; Nose, Tadao (Magnetic resonance imaging, 2002)
This study was aimed to investigate the significance of absolute concentration of metabolites in glioma patients using proton MR spectroscopy (MRS) with T2 relaxation time correction using three different echo times. The absolute concentrations of metabolites in 7 normal subjects and in 23 gliomas (10 low-grade, 13 high-grade) were obtained by proton MRS using a tissue water signal as an internal standard. The signal intensities of metabolites and tissue water were corrected by T2 relaxation time. In low-grade glioma, the T2 relaxation time of NAA was shorter, and T2 relaxation time of water was prolonged as compared to normal subjects (p < 0.001). In high-grade glioma, the T2 relaxation time of NAA (p < 0.001) and T2 relaxation time of Cr (p < 0.01) were shorter, and T2 relaxation time of water (p < 0.001) was prolonged as compared to normal subjects. Moreover, high-grade gliomas revealed a shorter T2 relaxation time of Cr than low-grade gliomas (p < 0.05). In glioma, NAA and Cr concentration were decreased, and Cho were increased as compared to normal subjects. Moreover, high-grade glioma revealed a significant lower Cr (p < 0.001) and Cho (p < 0.01) concentration compared to low-grade gliomas. Low Cr concentration is the most reliable indicator of malignancy in glioma. Cho concentration did not correlate with malignancy in gliomas.